In vivo n-methyl-d-aspartate receptor (NMDAR) density as assessed using positron emission tomography during recovery from NMDAR-antibody encephalitis - Galovic, M; Al-Diwani, A; Vivekananda, U; Walker, MC; Irani, SR; Koepp, MJ (American Medical Association, 2022)
N-methyl-d-aspartate receptor (NMDAR) autoantibodies are a common cause of autoimmune encephalitis. In vitro and animal studies indicated that NMDAR internalization is a major mechanism underlying NMDAR-antibody encephalitis, but direct support in humans is limited to a reduction of NMDAR staining in postmortem hippocampi.